A scare in the city - Chanek, Sherilin; Gutierrez, Rudy (Carmel, CA : Hampton-Brown, 2000)
The power goes out in the city. See how people react and the role that the police and firefighters take to help keep the city safe until the power is back on.
Keywords: Children's stories